Last Kingdom Season 1 Disc 1 - Dreymon, Alexander, 1983-; Dawson, David, 1982-; Cox, Emily; Macfadyen, Matthew; Universal Pictures Home Entertainment (Firm) (Universal City, CA Universal Pictures Home Entertainment, 2016)
The re-telling of the valiant story of King Alfred the Great and his desire to unite many separate kingdoms into what would become England. Combining real historical figures and events with fictional characters, it is the story of how a people reclaimed their land from the invading Vikings and built a place they call home.
Based on the bestselling novels by Bernard Cornwell.
Anamorphic widescreen (1.78:1).
Bonus features: creating the world of the The last kingdom; The making of The last kingdom; the stunts of The last kingdom.
Alexander Dreymon, David Dawson, Emily Cox, Matthew MacFadyen, Ian Hart.
CHV rating: 14A.
DVD.
Keywords: Great Britain -- History -- Drama; Drama; Fiction television programs; Historical television programs; History; Video recordings for the hearing impaired